Design of HOTS-Based Learning Evaluation for Ensemble Musical Instruments in the Form of Quizizz Application at MTS 2 Negeri Medan - Sri Wahyuni; Yudi Sukmayadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to develop a learning evaluation design for ensemble musical instruments based on Higher Order Thinking Skills (HOTS) using the Quizizz application at MTS 2 Negeri Medan. The background of the problem faced is the use of conventional evaluation methods that are less effective in measuring students' critical thinking abilities. This study employs a qualitative approach with a descriptive design, involving validation from subject matter experts and media experts, as well as a usability test involving 32 students. The results indicate that the developed evaluation design meets the feasibility criteria with an average score of 4.0 from subject matter experts and 4.7 from media experts, as well as an average score of 4.5 from the usability test, indicating that the Quizizz application can enhance student motivation and engagement in learning. The discussion emphasizes the importance of integrating technology in learning evaluation to create an interactive and engaging learning experience. The conclusion of this research is that the HOTS-based evaluation design developed is feasible to implement and can improve the quality of ensemble musical instrument learning, as well as provide recommendations for the application of similar methods in other schools and further research on the use of technology in education.